2000
DOI: 10.1073/pnas.011404498
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Acid-sensing ion channel 3 matches the acid-gated current in cardiac ischemia-sensing neurons

Abstract: Cardiac afferents are sensory neurons that mediate angina, pain that occurs when the heart receives insufficient blood supply for its metabolic demand (ischemia). These neurons display enormous acid-evoked depolarizing currents, and they fire action potentials in response to extracellular acidification that accompanies myocardial ischemia. Here we show that acid-sensing ion channel 3 (ASIC3), but no other known acid-sensing ion channel, reproduces the functional features of the channel that underlies the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 36 publications
(57 reference statements)
3
63
0
Order By: Relevance
“…It has been reported that the ischemic and inflamed areas in the body have a lower pH (<6.7) than the surrounding tissues and blood (pH ¼ 7.4) [24,25]. If a nanoparticle can release bFGF in a sustained way in the ischemic and inflamed areas (pH<6.7), and then rapidly disintegrate after repairing the tissue (pH ¼ 7.4), this nanoparticle might be useful as an intelligent, controlled release material.…”
Section: Ph-responsive Characteristics Of Nanoparticlesmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the ischemic and inflamed areas in the body have a lower pH (<6.7) than the surrounding tissues and blood (pH ¼ 7.4) [24,25]. If a nanoparticle can release bFGF in a sustained way in the ischemic and inflamed areas (pH<6.7), and then rapidly disintegrate after repairing the tissue (pH ¼ 7.4), this nanoparticle might be useful as an intelligent, controlled release material.…”
Section: Ph-responsive Characteristics Of Nanoparticlesmentioning
confidence: 98%
“…The CS/g-PGA and HP-CS/g-PGA nanoparticles were dispersed in distinct dissolution media (pH 6.0, 6.6 and 7.4 of buffer solutions, simulating the pH environments in ischemia tissue, critical ischemic tissue and normal tissue respectively) [24,25], and the dispersive stabilities of the nanoparticle were evaluated by turbidity measurement using a UVeVis spectrophotometer (Uvikon923, Kontron Instruments, Italy) at 500 nm [26]. The mean particle sizes and zeta potential values of nanoparticles were measured using a Zetasizer as abovementioned method.…”
Section: Stability Of Prepared Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient currents are highly sensitive to protons, with a pH 50 of around 6.5 [65, 69]. Electrophysiological studies have shown that ASIC3 subunits function as homomeric or heteromeric channels in sensory neurons [16, 7075]. They can sense extracellular acidification occurring under physiological or pathological conditions, such as cutaneous touch, pain perception, inflammation, and ischemia [70, 74, 7682].…”
Section: Electrophysiology Of Asicsmentioning
confidence: 99%
“…Electrophysiological studies have shown that ASIC3 subunits function as homomeric or heteromeric channels in sensory neurons [16, 7075]. They can sense extracellular acidification occurring under physiological or pathological conditions, such as cutaneous touch, pain perception, inflammation, and ischemia [70, 74, 7682]. For example, ASIC3 channels expressed in cardiac sensory neurons can respond to myocardial ischemia [70, 75, 82].…”
Section: Electrophysiology Of Asicsmentioning
confidence: 99%